Contextuality and Community: Challenges for Theological Education and Ecumenical Formation - Ortega Suárez, Ofelia (International review of mission, 2009)
This article looks at some aspects of the history of ecumenical theological formation. It emphasizes the need to strive for quality theological education. This should always be ecumenical and pluralistic, link the global and the local and be founded on community-based ecclesiastical theory. It points out the need to continue questioning the epistemological fundamentals of theology in order to ensure the continuous strengthening of the relationship between theory and practice. Another essential aspect is the relationship between mission and ecumenical theological formation and our understanding that education and ecumenical training is aimed at transforming people and communities. This means that changes to our educational institutions are indispensable. They should promote ecumenical, pluralist, inter-disciplinary and holistic policies and practices and a commitment to a radical interpretation of the Bible that leads us to seek justice and well-being for all people, communities and groups, and oppose any beliefs, practices and interpretation of the Bible that lead to oppression and injustice.